Innate Immune Responses Activated in Arabidopsis Roots by Microbe-Associated Molecular Patterns - Millet, Yves A; Danna, Cristian H; Clay, Nicole K; Songnuan, Wisuwat; Simon, Matthew D; Werck-Reichhart, Danièle; Ausubel, Frederick M (The Plant cell, 2010)
Despite the fact that roots are the organs most subject to microbial interactions, very little is known about the response of roots to microbe-associated molecular patterns (MAMPs). By monitoring transcriptional activation of β-glucuronidase reporters and MAMP-elicited callose deposition, we show that three MAMPs, the flagellar peptide Flg22, peptidoglycan, and chitin, trigger a strong tissue-specific response in Arabidopsis thaliana roots, either at the elongation zone for Flg22 and peptidoglycan or in the mature parts of the roots for chitin. Ethylene signaling, the 4-methoxy-indole-3-ylmethylglucosinolate biosynthetic pathway, and the PEN2 myrosinase, but not salicylic acid or jasmonic acid signaling, play major roles in this MAMP response. We also show that Flg22 induces the cytochrome P450 CYP71A12-dependent exudation of the phytoalexin camalexin by Arabidopsis roots. The phytotoxin coronatine, an Ile-jasmonic acid mimic produced by Pseudomonas syringae pathovars, suppresses MAMP-activated responses in the roots. This suppression requires the E3 ubiquitin ligase COI1 as well as the transcription factor JIN1/MYC2 but does not rely on salicylic acid-jasmonic acid antagonism. These experiments demonstrate the presence of highly orchestrated and tissue-specific MAMP responses in roots and potential pathogen-encoded mechanisms to block these MAMP-elicited signaling pathways.